Formulation of wound healing product from keratin protein - Nurdinie, Md Baliami (2013)
Every year billion of chickens will be commercially grown up and processed worldwide. These chickens when processed will leave billion pounds of unused feathers. The challenge is to turn the white plumes into usable items or valuable products. In this research, keratin protein will be extracted from the unused chicken feathers and then will be used in the formulation of effective wound healing product. This research intends to achieve three main goals. Firstly, to formulate wound healing product contains keratin protein, to produce an effective wound healing product to heal the wound and to determine the best formulation of wound healing product. The overall process to produce a hydrogel sheet are as the following. First of all, the main solutions need to be prepared one by one. The main solutions are chitosan, polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) solutions. Next, the hydrogel sheet was produced by mixing all the solution together with the continuos stirring on a hot plate stirrer for about 2-3 hours. After that, the samples were dried in an oven at room temperature. The fully dried hydrogel sheets were removed from the petri dish by using a forcep